â€œLatex Gloveâ€ Laparoscopic Pyeloplasty Model: A Novel Method for Simulated Training - Raza, Syed Johar; Soomroo, Kashifuddin Q; Ather, Mohammad Hammad (Urology Journal, 2011)
Purpose: To present a ’latex glove’ laparoscopic pyeloplasty (LPP) training model and determine its construct validity for its effective use in resident training. Materials and Methods: The ’latex glove’ model was used to perform LPP by five operators with variable level of experience, ranging from an experienced (> 20 independent LPPs) to minimal operative experience (year 5 medical student). The palm of the glove was considered the renal pelvis with finger of the glove as the proximal ureter. A knot at the junction of the two was considered as ureteropelvic junction obstruction. A basic lap trainer was used to simulate the LPP. Operation time was noted in minutes and quality of continuous suturing was determined for each operator, using a previously described nonvalidated scoring system by a blinded reviewer. Results: The operation time varied from 47 to 160 minutes for the most to the least experienced operator, and the difference was statistically significant (P = .043), while the quality of suturing score ranged from 1 to 6 for the most to the least experienced operator, respectively (P = .038). The operation time and quality of suturing were negatively correlated with the level of experience (-0.962 and -0.987, respectively), which were statistically significant (P = .009 and P = .002, respectively). Conclusion: This novel training model has proven its validity, as a cost-effective and readily available option for LPP training.